(untitled) (London Journal of Engineering Research, 2023)
This comprehensive study delves into the multifaceted landscape of modern power systems, encompassing their intricate infrastructure, the integration of smart grid technology for optimized energy management, the critical significance of cybersecurity in safeguarding against a plethora of cyber threats, and the identification of gaps in the deployment of effective cybersecurity measures. The investigation delves into three primary deployment clusters, focusing on system operation continuity protection, network security, and data protection, each pivotal in ensuring smart grids’ secure and seamless operation. Moreover, the study underscores the importance of frequency bias tie line control in maintaining stability within interconnected grids and addresses the evolving tactics of cyber attackers in exploiting vulnerabilities in power systems. By assessing recent cyber-physical compromise incidents and their cascading consequences, the research highlights the urgency of robust defense strategies and the need for international collaboration in strengthening the resilience of power system smart grids. This comprehensive analysis culminates in a resounding call for fortified cybersecurity frameworks to safeguard the reliability of power supply in the face of evolving cyber threats.